The Challenge of AI in Teacher Education: A Students’ Perspective on Learning Assistance - Alina Turculeț (Educaţia 21)
The interest in AI technologies in education it is not exactly new. The AI technologies supported individualized and personalized learning from content delivery to feedback provision and progress supervision since the beginning of the 21st century. The pedagogical potential of AI was explored in relation to teaching assistance and personalized learning. Nevertheless, the evolution of generative AI opens the way for misinformation and mystification in the field of education. According to the definition of artificial intelligence, “AI systems are designed to simulate or replicate human cognitive functions and adapt to new information and situations”. Simulating and replicating does not mean replacing. If a few years ago, the biggest fear of a teacher was that the students would take fragments available on the internet, once with the evolution of AI, the biggest threat becomes that the cognitive abilities of the students would not be trained at all. Our study shows how students were challenged to use AI to produce scientific content related to curriculum theories. The results are in line with the international trend that depicts AI as a learning instrument, as an assistant for teaching and learning processes. The prospective teachers enhance that the content provided by an AI generative soft might impress a novice, but not an experienced person. However, they appreciated the design of the delivered content and the speed with which it was proposed.